Arbitrated quantum signature scheme with continuous-variable squeezed vacuum states - 冯艳艳;施荣华;郭迎 (Chinese physics B, 2018)
We propose an arbitrated quantum signature （AQS） scheme with continuous variable （CV） squeezed vacuum states, which requires three parties, i.e., the signer Alice, the verifier Bob and the arbitrator Charlie trusted by Alice and Bob, and three phases consisting of the initial phase, the signature phase and the verification phase. We evaluate and compare the original state and the teleported state by using the fidelity and the beam splitter （BS） strategy. The security is ensured by the CV-based quantum key distribution （CV-QKD） and quantum teleportation of squeezed states. Security analyses show that the generated signature can be neither disavowed by the signer and the receiver nor counterfeited by anyone with the shared keys. Furthermore, the scheme can also detect other manners of potential attack although they may be successful. Also, the integrality and authenticity of the transmitted messages can be guaranteed. Compared to the signature scheme of CV-based coherent states, our scheme has better encoding efficiency and performance. It is a potential high-speed quantum signature scheme with high repetition rate and detection efficiency which can be achieved by using the standard off-the-shelf components when compared to the discrete-variable （DV） quantum signature scheme.